Facile green synthesis of nanoparticles from brown seaweed Sargassum wightii and its biological application potential. (18th September 2018) - Deepak, Paramasivam; Amutha, Vadivel; Birundha, Rajendhiran; Sowmiya, Rajamani; Kamaraj, Chinnaperumal; Balasubramanian, Velramar; Balasubramani, Govindasamy; Aiswarya, Dilipkumar; Arul, Dhayalan; Perumal, Pachiappan
Abstract: Diabetes mellitus is a common metabolic disorder characterized by hyperglycemia and is a major cause of blindness, kidney failure, heart attack, stroke and is also responsible for lower limb amputation. The purpose of the present study was to evaluate the antioxidant and enzyme inhibitory efficacy of silver nanoparticles synthesized from brown alga, Sargassum wightii . The synthesized silver nanoparticles revealed spherical morphology with the size range of 18.45–41.59 nm. The green synthesized sliver nanoparticles of S. wightii were characterized through UV-visible spectroscopy, Fourier transform infrared spectroscopy, x-ray diffraction, field emission scanning electron microscopy, energy dispersive x-ray spectroscopy, zeta potential and by dynamic light scattering method. Presently, the enzyme inhibitory property of S. wightii -aqueous extract and synthesized silver nanoparticles of S. wightii against amylase and glucosidase was found to be 252.8 and, and 284.18 and, respectively. Similar trend of antioxidant activity have been recorded. The presently synthesized silver nanoparticle through green approach is an eco-friendly and cost effective one and it could form an effective pharmacological agent.